Memorial dedicated to Major General John Bellasis - Ghosh, Ayan (2023)
Memorial dedicated to Major General John Bellasis, who was the commander of the East India Company army at Mumbai and died on 11th February 1808, aged 64 years. The memorial is also dedicated to his wife, Anne Martha, who died in Mumbai on 14 May 1797. The couple got married at St. Thomas Church on 3rd June 1776. Bellasis Road in Mumbai is named after John Bellasis, who constructed it in 1793 as a famine relief effort.